Preferential Autoimmune Response in Prostate Cancer to Cyclin B1 in a Panel of Tumor-Associated Antigens. (17th April 2014) - Dai, Liping; Li, Jitian; Ortega, Rosalia; Qian, Wei; Casiano, Carlos A.; Zhang, Jian-Ying
Abstract : Previous studies have demonstrated that sera from patients with prostate cancer (PCa) contain autoantibodies that react with tumor-associated antigens (TAAs). Autoantibodies to cyclin B1 and fourteen other TAAs were detected by enzyme-linked immunosorbent assay (ELISA) and Western blotting in 464 sera from patients with PCa, benign prostatic hyperplasia (BPH), and other controls. Autoantibodies to cyclin B1 were detected in 31.0% of sera from randomly selected patients with PCa versus 4.8% in sera with BPH. In the further analysis, 31.4% of sera from PCa patients at the early stage contained anti-cyclin B1 autoantibody, and even 29.4% of patients who had normal prostate-specific antigen (PSA) levels in their serum samples were observed anti-cyclin B1 positive. The cumulative positive rate of autoantibodies against seven selected TAAs (cyclin B1, survivin, p53, DFS70/LEDGFp75, RalA, MDM2, and NPM1) in PCa reached 80.5%, significantly higher than that in normal control sera. In summary, autoantibody to cyclin B1 might be a potential biomarker for the immunodiagnosis of early stage PCa, especially useful in patients with normal PSA level. This study further supports the hypothesis that a customized TAA array can be used for enhancing anti-TAA autoantibody detection, and it may constitute a promising and powerful tool for immunodiagnosis of PCa.